1996
DOI: 10.1093/carcin/17.8.1567
|View full text |Cite
|
Sign up to set email alerts
|

ACCELERATED PAPER: Identification of human tumour suppressor genes by monochromosome transfer: rapid growth-arrest response mapped to 9p21 is mediated solely by the cyclin-D-dependent kinase inhibitor gene, CDKN2A(p16INK4A)

Abstract: Microcell transfer of intact normal human chromosomes into immortal mouse and hamster fibroblast cell lines has revealed growth suppressive activity associated with a small sub-set of the human complement. Here, we describe the results of a detailed study aimed at identifying the gene or genes responsible for the rapid growth-arrest response obtained with human chromosome-9. Initially, STS-PCR deletion mapping of segregants arising in monochromosome transfer experiments was used successfully to localize the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…On the other hand, p16 has many of the attributes expected of a senescence mediator and it has recently been reported that ®broblasts from p16 nullizygous mice immortalize at a very high frequency, presumably indicative of a failure to senesce (Serrano et al, 1996). Moreover, the higher frequency of p16 deletions and mutations observed in human tumour cell lines as opposed to primary tumours likely re¯ects selection in culture, as a means of escaping senescence, and several studies have provided good evidence for a correlation between loss of p16 function and immortalization (Loughran et al, 1994(Loughran et al, , 1996Rogan et al, 1995;England et al, 1996;Noble et al, 1996;Rezniko et al, 1996). Although the current data imply that this selective pressure may be less critical for mouse cells, there is evidence that the mouse p16 gene also acts as a tumour suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, p16 has many of the attributes expected of a senescence mediator and it has recently been reported that ®broblasts from p16 nullizygous mice immortalize at a very high frequency, presumably indicative of a failure to senesce (Serrano et al, 1996). Moreover, the higher frequency of p16 deletions and mutations observed in human tumour cell lines as opposed to primary tumours likely re¯ects selection in culture, as a means of escaping senescence, and several studies have provided good evidence for a correlation between loss of p16 function and immortalization (Loughran et al, 1994(Loughran et al, , 1996Rogan et al, 1995;England et al, 1996;Noble et al, 1996;Rezniko et al, 1996). Although the current data imply that this selective pressure may be less critical for mouse cells, there is evidence that the mouse p16 gene also acts as a tumour suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…The repeated loss of exogenous, wild type, chromosome alleles in immortal segregant clones arising from MMCT experiments can indicate that there is a suppressor of cancer cell proliferation (England et al, 1996) or viability (Robertson et al, 1998) in that chromosome region and can be used to map the position of the genes. This approach has been successfully used to map the gene responsible for Leigh Syndrome (Zhu et al, 1998).…”
Section: The Loss Of Exogenous Chromosome 4 Alleles Is Related To Thementioning
confidence: 99%
“…The TSG is either introduced into tumour cells as a cloned cDNA in an appropriate expression vector 104 or as an individual chromosome by microcell-mediated transfer. 105 Introduction of a retroviral vector containing normal wild type RB cDNA into the PC cell line DU145 resulted in an approximately 15-fold reduction in the tumorigenicity of the transfectants in nude mice.…”
Section: Retinoblastoma Tsgmentioning
confidence: 99%